A Human Occupation Cave During the Bronze Age: Archaeological and Palynological Applications of a Case Study in Sardinia (Western Mediterranean). (26th September 2014) - Buosi, C.; Pittau, P.; Paglietti, G.; Scanu, G. G.; Serra, M.; Ucchesu, M.; Tanda, G.
Abstract : Investigation of a prehistoric settlement in the south‐western Sardinia area attests to human occupation by the Nuragic civilization in a cave during the Early and Middle Bronze Age. An occasional human presence is recorded from the Early Bronze Age and a continued one relating to rural (cultivation, storage) and domestic (ceramic, metallurgy) activities is documented in the Middle Bronze Age. These distinct settlement phases have been radiocarbon‐dated and palynologically recognized. In addition, pollen analysis suggests that a degraded forest was present during the Middle Bronze Age in south Sardinia prior to central Sardinia, which is probably related to a hot climate and a regime of low annual precipitation. The data reveal a climate‐induced deforestation phase that is likely to be emphasized by anthropogenic pressure.